The Role of the ILO during and after Apartheid. (December 2021) - Webster, Edward; Forrest, Kally
The International Labour Organization (ILO) at times played an important role in challenging race discrimination in the workplace, both as apartheid legislation intensified and in the new democratic South Africa. The controversy around forced labor, and the participation of independent African countries in the ILO, ultimately led to the withdrawal of South Africa. Subsequently, ILO Conventions and the 1964 Declaration influenced the government to establish the 1978 Wiehahn Commission to examine industrial relations. Its recommendations led to extensive unionization. The ILO was initially reluctant to recognize the independent unions but subsequently worker organizational power led to its support. Later, it contributed to creating a post-apartheid workplace order. However, despite its intention to build an inclusive industrial relations system, many workers remain excluded from the regulatory framework and the labor movement. The ILO's rigid binary between direct coercion on the one hand and the voluntary recruitment of workers on the other does not capture the continuity from slavery, indentured labor, and the migrant labor system through to use of casual labor in contemporary South Africa. The ILO seems more comfortable with traditional unions and clear-cut employer-employee relationships.